A Queer Tension: The Difficult Comedy of Hannah Gadsby: Nanette. Issue 1 (10th May 2021) - Jenzen, Olu
Abstract : This article concerns itself with feminist comedy that is deemed angry and difficult in an era of postfeminism. Hannah Gadsby's live show Nanette, released as a Netflix film, can be described as difficult because it is politically challenging, emotionally demanding and disrupts the established format of stand-up comedy. Yet it has had critical and commercial success. Nanette challenges the underpinning assumption of postfeminism: that feminism is no longer needed. It is feminist and angry. To explore the phenomenon of angry feminist comedy in the postfeminist era, the article considers the comedy of Gadsby through the figure of the feminist killjoy, coined by Sara Ahmed, to reflect how the killjoy and the queer art of failing offer forms of political 'sabotage' that subvert comedy as masculinist popular culture.